Analysis of the degree of formalization and automation of design - Барабаш, М.С.; Дзюба, А.В. (Proceedings of National Aviation University (archive), 2007)
Development of information and logical model which allows to carry out alternative designing is offered, to estimate the received variants, to select from them the most rational, to give to the expert exhaustive information for a choice of a suitable variant.